2018
DOI: 10.1002/cmdc.201700640
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Indolactam V Analogues as Inhibitors of PAR2‐Induced Calcium Mobilization in Triple‐Negative Breast Cancer Cells

Abstract: Human proteinase-activated receptor 2 (PAR2), a transmembrane G-protein-coupled receptor (GPCR), is an attractive target for a novel anticancer therapy, as it plays a critical role in cell migration and invasion. Selective PAR2 inhibitors therefore have potential as anti-metastatic drugs. Knowing that the natural product teleocidin A2 is able to inhibit PAR2 in tumor cells, the goal of the present study was to elaborate structure-activity relationships and to identify potent PAR2 inhibitors with lower activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…ENMD-1068 decreases in MCF-7 breast cancer cells the concentrations of granulocyte colony-stimulating factor (GCSF), a highly expressed cytokine correlated with poor survival [113,114]. Recently, structure–activity relationship studies have allowed the identification of promising selective PAR2 inhibitors including derivatives of teleocidin with high efficacy in inhibiting breast tumor cell migration [115]. Whether PAR2 antagonists could be considered as PAR1 antagonists and vice versa is a matter of interest given that PAR2 interacts with PAR1 to form a functional unit implied in breast tumor development [116].…”
Section: Gpcrs In Breast Cancer: Signaling Biology and Modulatorsmentioning
confidence: 99%
“…ENMD-1068 decreases in MCF-7 breast cancer cells the concentrations of granulocyte colony-stimulating factor (GCSF), a highly expressed cytokine correlated with poor survival [113,114]. Recently, structure–activity relationship studies have allowed the identification of promising selective PAR2 inhibitors including derivatives of teleocidin with high efficacy in inhibiting breast tumor cell migration [115]. Whether PAR2 antagonists could be considered as PAR1 antagonists and vice versa is a matter of interest given that PAR2 interacts with PAR1 to form a functional unit implied in breast tumor development [116].…”
Section: Gpcrs In Breast Cancer: Signaling Biology and Modulatorsmentioning
confidence: 99%
“…Sunitinib, a kinase inhibitor, was found to inhibit downstream CDC42 and RHO kinases 1 (ROCK1) functions by targeting G Protein-Coupled Receptor Kinase 5 (GRK5) to modulate the motility of triple-negative breast cancer cells [ 161 ]. Jan Stein et al found that teleocidin A2 can inhibit proteinase-activated receptor 2 (PAR2) in breast cancer [ 162 ]. Similarly, a coenzyme Q10 analog, decylubiquinone, was found to inhibit brain angiogenesis inhibitor 1 in breast cancer, thus inhibiting metastasis [ 163 ].…”
Section: Defined Emt Molecules In Cancermentioning
confidence: 99%